Attentional vigilance of food information in disordered eating behaviors - Jin, Luyao; Han, Wenyue; Zheng, Zheng (Frontiers in Psychiatry, 2023)
We studied attentional bias (AB) to food information in disordered eating behaviors (DEBs). The DEB group (n = 29) with high scores and the healthy control (HC) group (n = 25) with low scores in the Eating Attitudes Test-26 (EAT-26) completed the Exogenous Cueing Task (ECT). The ECT evaluated their reaction time (RT) to the location of a target dot preceded by a food or neutral cue. The study found that compared with HC group, DEB group showed more attentional engagement to food stimuli. The results of the current study indicate that attentional vigilance to food information could be considered as a specific AB of individuals with DEBs. Our findings not only provide evidence of potential mechanisms affecting DEBs from the perspective of attentional bias, but also can be considered as an effective and objective indicator for early screening of subclinical eating disorders (EDs).